Revitalisasi Tradisi Ijtihad dalam Pendidikan Islam: Membangun Nalar Progresif dan Kreativitas Intelektual di Era Modern - Assagaf, Muhammad Ridha (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the revitalization of the ijtihad tradition in Islamic education as a progressive paradigm of thinking in the modern era. Using a systematic literature review approach of SINTA-indexed journals (2019–2024) and classical Islamic thought, the research found that ijtihad plays a fundamental role in developing rationality, creativity, and moral awareness among students. The revitalization of ijtihad in Islamic education includes curriculum renewal based on maqashid al-shariah, reflective and contextual learning models, and strengthening the teacher’s role as a mujtahid tarbawi. Findings reveal that Islamic education grounded in ijtihad values fosters ulul albab learners who are critical, ethical, and adaptable to global changes. Thus, ijtihad is not merely a legal instrument but also a pedagogical methodology to integrate faith, knowledge, and action in modern learning.